Recycling Mining Rope Waste Karama Village, Tinambung District, Polewali Mandar Regency, West Sulawesi Province - Jamal, Abd; Siadina, Siadina; Dahniar, Dahniar; Ali, Najmah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Rope recycling craft is a productive economic activity that utilizes raw materials from weathered rope waste which is recycled into new rope. The urgency of this community empowerment activity is carried out, apart from reducing the impact of rope waste on the environment it can also provide an opportunity for each community to be able to develop their potential and try to increase their income. The problem faced by Partners is a lack of skills in increasing quality production and marketing. The objectives of this activity are 1) to improve partners' skills regarding production and 2) to improve human resource capabilities in marketing. Solutions and Targets The final result to be achieved in this activity is to increase partners' skills in producing and marketing high quality and sustainable ropes. The purpose of this service and empowerment program activity. Improving the skills of partner group members in increasing the production and marketing of their business results. know the rope production system in Karama Village, Polewali Mandar Regency to meet existing market demand in terms of technological developments and Green Economy principles as well as the level of employment for the people of Karama Village. The methods applied to overcome these problems are through counseling, training with demonstrations of recycling rope waste, as well as mentoring and mentoring to make products ready for market. The activity was carried out on 14-15 August 2023 at the business location of the Siasayangi Business Group, Karama Village, Tinambung District, Polewali Mandar Regency. Activities consisted of participatory counseling coupled with demonstrations of recycling rope waste. The results of recycling this rope waste can also be sold so that it can increase income and improve the family's economy. Recycling rope requires patience, patience, and innovation, and training is still needed